The Role of Digitalization in Enhancing Green Innovation Efficiency: Examination of Multiple Sub-Dimensions, Transformation Speed, and Heterogeneity - Tingqian Pu (SAGE Open)
Enhancing the efficiency of green innovation is a vital step toward sustainable progress and eco-conscious economic growth. Using data from Chinese listed firms between 2007 and 2022, this study explores how digitalization influences corporate green innovation efficiency. The analysis indicates a significant positive effect of digitalization, particularly on firms in non-manufacturing industries and those located in developed regions. Key digitalization components, including cloud computing and digital technology applications, emerge as pivotal in improving green innovation efficiency, whereas technologies like artificial intelligence, blockchain, and big data face implementation challenges. Additionally, the speed of digitalization is shown to amplify these benefits. These findings provide valuable evidence and actionable policy recommendations to utilize digitalization for promoting green economic growth and sustainable development. JEL Classification: G34, O31, O32, O33.